2013
DOI: 10.1016/j.jaapos.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amblyopia treatment on stereoacuity

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 30 publications
6
38
3
2
Order By: Relevance
“…18,19 Stereoacuity can be improved with treatment of amblyopia. 20 However, in our study, amblyopia was not a predictive factor for failure in recovery of stereopsis (p = 0.22). Binocular dysfunction is primary and monocular visual acuity loss is secondary.…”
Section: Resultscontrasting
confidence: 72%
“…18,19 Stereoacuity can be improved with treatment of amblyopia. 20 However, in our study, amblyopia was not a predictive factor for failure in recovery of stereopsis (p = 0.22). Binocular dysfunction is primary and monocular visual acuity loss is secondary.…”
Section: Resultscontrasting
confidence: 72%
“…For example, Richardson, Wright, Hrisos, Buck, and Clarke (2005), found that refractive correction alone resulted in an 30 arc s improvement in stereoacuity in non-strabismic amblyopic children between the ages of 3 and 4 years, 9 months. This improvement in stereopsis from refractive correction alone (often referred to as refractive adaptation) has been confirmed by other studies (Stewart et al, 2013). Importantly the improvement is not limited to anisometropic amblyopia, but also extends to strabismic amblyopia.…”
Section: Can Stereopsis Be Recovered In Children and Adults With Asupporting
confidence: 79%
“…In addition, some of the studies may have confounded treatments. For example, as noted above, in children, spectacle correction alone can improve visual acuity and stereoacuity (Richardson et al, 2005; Stewart et al, 2013). Amblyopic subjects, upon entry to a study are often refracted and given an updated spectacle correction.…”
Section: Summary Caveats and Conclusionmentioning
confidence: 94%
“…Regardless of the mechanism behind optical treatment of strabismic amblyopia, the fact that considerable gains in acuity and stereopsis can be achieved places optometrists at the frontline of treatment. A useful field guide, informed by sound empirical evidence, has been complied by Chen and Cotter .…”
mentioning
confidence: 99%